Oxidized Hyaluronic Acid Hydrogels as a Carrier for Constant-Release Clenbuterol Against High-Fat Diet-Induced Obesity in Mice - Chen, Wei-Yao; Lin, Feng-Huei (Frontiers in Endocrinology, 2021)
The global obesity population is increasing year-by-year, and the related cost is sharply increasing annually. There are several methods available to combat obesity; however, there is a lack of a single tool that is both safe and efficacious. The use of Clenbuterol in bodybuilding and by professional athletes is controversial owing to its side effects, including hepatotoxicity. This study administered Clenbuterol at a much lower dose than the established safety level, and rather than through oral administration, the treatments were delivered through controlled-release intra-adipose injection. The different dosing and mode of administration will lower the risk of side effects, increase the safety profile, and could facilitate use in the anti-obesity market. A thermo-sensitive hydrogel was used as the carrier uploaded with Clenbuterol to achieve controlled-release. In the in vitro study, the developed new formulae were not cytotoxic to 3T3-L1 cells and could inhibit lipogenesis effectively. In the animal study, the mice were fed a high-fat diet and treated with Clenbuterol by oral administration, or injected with Clenbuterol-modified hyaluronate hydrogel (HAC) regularly. Both groups showed reduction in whole-body, visceral, and gonadal fat contents and body weight. The abdominal fat was analyzed using MRI imaging in adipose mode and water mode. The abdominal fat ratio in the mice treated with normal diet and those given intra-adipose injections with HAC had the lowest value among the test groups. The mice treated with high-fat diet (HFD) showed the highest value of 53.78 %. The chronic toxicity in-vivo test proved that controlledrelease injections of 2 g -10 g Clenbuterol daily were safe, as demonstrated in the blood elements and serological analyses. This study developed a new and promising method for anti-obesity treatment, using a monthly intra-adipose controlled-release injection of HAC. The developed new formulae of Clenbuterol not only effectively decreased body weight and body fat content but also inhibited lipogenesis on the harvested visceral tissue and reduced adipose tissue around the gonadal area. The side effects induced by traditional oral administration of Clenbuterol were not observed in this research; this has excellent potential to be a useful tool for future obesity treatment without safety concerns.